Integrasi Syariat dan Tasawuf dalam Otoritas Keulamaan Abdurrauf As-Singkili: Kajian Historis atas Transmisi Jaringan Ulama Haramain–Nusantara Abad ke-17 - Zulfa Uswatun Hasanah; Nur Saidah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Existing studies on Abdurrauf As-Singkili have generally focused on his scholarly network, Sufi thought, or intellectual works separately, while the integration of sharia and Sufism as a foundation of his religious authority within the Haramain–Nusantara scholarly network remains relatively underexplored. This study aims to analyze the integration of sharia and Sufism in the construction of Abdurrauf As-Singkili’s religious authority in the seventeenth century and its relevance to contemporary Islamic education. Employing a historical method with a qualitative library research approach, the study draws upon secondary sources, including books, scholarly journal articles, and previous research. The data were analyzed through the stages of heuristics, source criticism, interpretation, and historiography. The findings indicate that Abdurrauf’s religious authority was shaped through the transmission of knowledge within the Haramain–Nusantara scholarly network, which connected the intellectual traditions of the Middle East and Aceh. The integration of sharia and Sufism constituted an important foundation of his thought, reflected in his roles as a mufti, educator, Shattariyah Sufi master, and author of Islamic works. This integration was manifested not only in his intellectual contributions but also in his da'wah and educational activities in seventeenth-century Aceh. Furthermore, the study suggests that the relationship between the normative and spiritual dimensions of Islam in Abdurrauf’s thought may provide a useful perspective for the development of Islamic education that balances intellectual, moral, and spiritual aspects.